2003
DOI: 10.1177/1049732303013005006
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing a Meaning of Pain: Older Korean American Women's Experiences with the Pain of Osteoarthritis

Abstract: The purpose of this grounded theory study was to gain a deeper understanding of older Korean American women's experiences of chronic osteoarthritic pain. The data included a set of 3 interviews with 7 women over age 60, field notes, observations, memos, and the literature about the chronic pain of osteoarthritis. Through constant comparative analysis and coding typical of grounded theory, a five-stage process emerged inductively from the data. The core variable, Reconstructing a Meaning of Pain, included the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 23 publications
0
30
0
1
Order By: Relevance
“…, Ojala et al . ); nine studies of musculoskeletal/arthritis ( n = 281) (Dickson & Kim , Hwang et al . , Afrell et al .…”
Section: Resultsmentioning
confidence: 99%
“…, Ojala et al . ); nine studies of musculoskeletal/arthritis ( n = 281) (Dickson & Kim , Hwang et al . , Afrell et al .…”
Section: Resultsmentioning
confidence: 99%
“…I am still me and can enjoy my life When I finally did accept the fact that, okay, I wasn't going to be able to (28,35,42,61,70,71,68,69,96,99,104,107) work and that I was going to have to do things differently ... I shifted my energies ... to the stuff that gives me pleasure (96).…”
Section: Conceptual Categoriesmentioning
confidence: 99%
“…There must be some other reason I feel that, all these rigid things that you try and put in place to protect (28,29,32,34,39,70,73,89,93,94,103 yourself, quite often are actually a problem that you have in your mind rather 108,113,115) than your back. So I think your mind and your back are quite closely linked (93).…”
Section: Conceptual Categoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dickson and Kim also found this reticence in their cohort of Korean-American women living with chronic osteoarthritic pain. 20 Blomqvist and Edberg interviewed elderly folk who lived with chronic pain and found that pain threatened these people's self-image as independent individuals. 21 A large percentage of these people tried to hide the pain with silence and a reluctance to complain.…”
Section: Discussionmentioning
confidence: 99%